The new design and technological solutions for the led modules for retrofit lamps - B. M. Борщов; А. М. Листратенко; И. Т. Тымчук; M. A. Проценко; Г. И. Никитский; А. А. Фомин; Л. А. Назаренко; В. М. Сорокин; А. В. Рыбалочка; А. С. Олейник (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
The authors propose fundamentally new design-technological solutions for compact volumetric mirrorized LED modules with increased power. Test samples of volumetric light-effective LED light effective modules with a power of 10–15 W and light output of 105–160 lm/W for domestic retrofit lamps based on high-efficiency SMD, mini COB, and COB LEDs of third generation were manufactured and tested. Positive technical and practical results were obtained by increasing by over 4–6 times the size of holders — heat sinks (compared to LED modules of flat holders) for heat dissipation from the LEDs by conduction and heat radiation, as well as by increasing light efficiency of LED lamps due to the additional light re-reflection by mirrorized reflectors-radiators in the bulb which is diffuser of the lamp light.